Social Work in Zimbabwe: From Social Control to Social Change - Noel G Muridzo; Rudo Memory Mukurazhizha; Samuel Lisenga Simbine (International Federation of Social Workers, 2023)
While human rights and social justice are critical in any social worker’s thinking and actions, the history of social work in Zimbabwe shows how the profession has perpetuated human rights violations and social injustice. This article chronicles the historical development of social work in Zimbabwe, highlighting instances where social work not only contributed to and/or perpetuated colonialism but also human rights violations and social injustice. Using examples of past and current social work interventions, the article argues that professionals may knowingly or unknowingly keep the status quo. In Zimbabwe, social work comes into being an agent of social control, dealing with school truancy, children in conflict with the law, and offering means-tested public assistance among other services segregated on racial lines. Social work has also been used by the independent majority government as an instrument of social change to expand opportunities and address social inequalities. This article observes that social work in Zimbabwe was thus used both as an agent of social control advancing the colonial agenda and as an agent of social change tackling social injustices such as poverty and inequality. We conclude that social work has a role in challenging oppression, and it must always distance itself from being used as a tool in the hands of oppressors.